Analisis Ketimpangan Pendapatan dan Kemiskinan di Sumatera Utara (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study is to evaluate income inequality and poverty as key indicators of uneven economic development in North Sumatra Province in 2024. This study analyzed various secondary sources, including BPS reports, SINTA-indexed national journals, and regional economic policy publications. The results show that regencies in the west coast and mountainous regions of North Sumatra tend to be lagging behind, while urban areas such as Medan and Deli Serdang have the highest concentration of economic growth, meaning that income inequality remains at a moderate-high level. The finding that economic progress remains uneven is reinforced by the fact that the poverty rate remains higher than the national average. From the results of this study, not only economic factors influence inequality and poverty, but also structural factors such as infrastructure access, human labor quality, and regional fiscal inequality. Therefore, more inclusive and integrated policies are needed to address inequality and improve welfare across all provinces.